Evaluasi Laju Korosi dan Estimasi Remaining Life Material ASTM A333 Grade 6 pada Sistem Transmisi Gas Menggunakan Metode Corrosion Coupon - Miftahul Habibil Fajri; Lisa Puspita Ariyanto; Meryanalinda Meryanalinda (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Internal corrosion is a key factor affecting the integrity and reliability of gas transmission pipelines. This study evaluates the corrosion rate and estimates the remaining life of ASTM A333 Grade 6 material using the weight loss-based corrosion coupon method. Measurements were conducted at three locations: an offshore platform (CC-01), a riser/subsea transition section (CC-02), and an onshore receiving station (CC-03), with a 30-day exposure period. Corrosion rates were determined according to ASTM G31, while remaining life was estimated based on API 570 and ASME B31.8. The results showed corrosion rates of 0.846; 0.524; and 0.188 mpy, all classified as low. Estimated remaining life values were 97.65, 157.71, and 439.68 years. Low corrosion rates were associated with dry gas conditions, low CO₂ and H₂S partial pressures, and the absence of free water. The pipeline system remains within acceptable integrity limits. Accordingly, API 570 inspection intervals should be maintained to ensure reliability and safety.